Multifunctional sulfur-mediated strategy enabling fast-charging Sb2S3 micro-package anode for lithium-ion storage. Issue 12 (5th March 2021) - Wang, Shaohua; Cheng, Yong; Xue, Hongjin; Liu, Wanqiang; Yi, Zheng; Chang, Limin; Wang, Liming
Abstract : A micro-package anode composed of Sb2 S3 particles was encapsulated into S-doped expanded graphite (Sb2 S3 @EG′-S) by a sulfur-mediated route for energy storage applications. The performance at a high current density is superior to most previously reported Sb2 S3 -based anodes. Abstract : A rate-limited formation of low-stage intercalation and lithium precipitation at high C-rate severely limits the application of graphite anodes for fast-charging lithium ion batteries (LIBs). The exploration of a new-type of fast-charging anode is promising and urgent. Herein, a high-rate Sb2 S3 -based micro-package anode composed of Sb2 S3 particles encapsulated into S-doped expanded graphite (Sb2 S3 @EG′-S) is developed by a scalable sulfur-mediated route. The sulfur used here is multifunctional, which can not only act as a sulfur source for sulfurization and S-doping but also to assist the exfoliation of expanded graphite and to encapsulate the in situ transformed Sb2 S3 particles. It is demonstrated that the above sulfur-mediated strategy promotes the formation of a packaging structured composite with an average size of 9–15 μm and low BET specific surface area, exhibiting a high initial coulombic efficiency of 86.7%. Moreover, the advantages of well-distributed Sb2 S3 particles into the package, high conductivity, and reversibility endow the composite anode with fast-charging lithium storage capacity in both half and full LIBs. Very importantly, the capacity can be maintained at 548 mA h g −1 at 5 A g −1 over 100 cycles for half-cell and 71.3% at 4C rate for full-cell LIBs with NCM333 as the cathode.